Morphological and molecular evidence support a close relationship between the free-living archamoebae Mastigella and Pelomyxa - Zadrobílková, Eliška; Walker, Giselle; Čepička, Ivan (Protist, 2015)
Members of the archamoebae comprise free-living and endobiotic amoeboid flagellates and amoebae that live in anoxic/microoxic habitats. Recently, the group has been divided into four separate families, Mastigamoebidae, Entamoebidae, Pelomyxidae, and Rhizomastixidae, whose interrelationships have not been completely resolved. There still are several key members of the archamoebae, notably the genus Mastigella, from which sequence data are missing. We established 12 strains of 5 species of Mastigella and Pelomyxa in culture, examined their morphology and determined their actin gene sequences. In addition, we examined the ultrastructure of three strains and determined and analyzed SSU rDNA sequences of two strains. Our data strongly suggest that Mastigella is specifically related to Pelomyxa, and it is transferred into the family Pelomyxidae. Surprisingly, Mastigella is likely paraphyletic with Pelomyxa forming its internal branch. The two genera share several morphological features that point to their common evolutionary history. Three new species of Mastigella are described: M. erinacea sp. nov., M. rubiformis sp. nov. and M. ineffigiata sp. nov.
Keywords: Molecular Sequence Data; Archamoebae; Sequence Analysis, DNA; Pelomyxa; Actins; Mastigella; aktiny; DNA, Ribosomal; protozoální proteiny; Cluster Analysis; protozoální DNA; RNA ribozomální 18S; Protozoan Proteins; fylogeneze; RNA, Ribosomal, 18S; ribozomální DNA; sekvenční analýza DNA; molekulární sekvence - údaje; DNA, Protozoan; phylogeny.; Phylogeny; shluková analýza